2(3x-4)=8(2x+1)

Simple and best practice solution for 2(3x-4)=8(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-4)=8(2x+1) equation:


Simplifying
2(3x + -4) = 8(2x + 1)

Reorder the terms:
2(-4 + 3x) = 8(2x + 1)
(-4 * 2 + 3x * 2) = 8(2x + 1)
(-8 + 6x) = 8(2x + 1)

Reorder the terms:
-8 + 6x = 8(1 + 2x)
-8 + 6x = (1 * 8 + 2x * 8)
-8 + 6x = (8 + 16x)

Solving
-8 + 6x = 8 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
-8 + 6x + -16x = 8 + 16x + -16x

Combine like terms: 6x + -16x = -10x
-8 + -10x = 8 + 16x + -16x

Combine like terms: 16x + -16x = 0
-8 + -10x = 8 + 0
-8 + -10x = 8

Add '8' to each side of the equation.
-8 + 8 + -10x = 8 + 8

Combine like terms: -8 + 8 = 0
0 + -10x = 8 + 8
-10x = 8 + 8

Combine like terms: 8 + 8 = 16
-10x = 16

Divide each side by '-10'.
x = -1.6

Simplifying
x = -1.6

See similar equations:

| 11+7+x=35 | | 2X-X=20 | | 4+247=13-5 | | 230-6x=30x+18 | | 9-10=61-38x | | -7(-5p+4a)= | | 3x+4=52 | | 4(x+2)=2(2x+1)+6 | | f(x)=-x^3-2 | | 1.25+6x= | | 6.95-(1.95+0.10x)=0 | | -2(6+9)= | | 5x+11=5x-21 | | 4x^2+(31x)=0 | | 13-(x+8)=6x+2 | | 14.25/5 | | 14.25/4 | | 0.75x+.05(2-x)=10(43) | | -2(x+6)=0,5-14 | | 3x^2=5-2 | | 8399840909205709x=897979070979797009-5 | | 9=-27+4x | | -7-6x+2=-(x-4).+2(x+6) | | 4/3x=-3 | | -3(2t-5)+2t=5t | | 10=-27+4x | | 2x^2+4ax+3x+6a=0 | | 3468666765x-558575858=68687763456789+56789 | | 2x/5=-2 | | (3-x).5+8=18 | | 2x/5 | | -84-10x=56-38x |

Equations solver categories